Direct Synthesis of Primary Anilines via Nickel‐mediated C(sp2)‐H Aminations. Issue 7 (5th February 2018) - Yu, Lin; Chen, Xiang; Liu, Da; Hu, Liang; Yu, Yongqi; Huang, Hang; Tan, Ze; Gui, Qingwen
Abstract: An efficient and mild protocol for the direct conversion of arene C−H bonds to C−NH2 without the need for extra deprotection step has been established, and to the best of our knowledge, this is the first time that the synthesis of primary anilines via nickel‐mediated C( sp 2 )‐H activations has been reported. This approach utilizes 8‐aminoquinoline as the directing group and sodium azide, a cheap and commercially available material, as the nitrogen source. In addition, the reaction is highly selective, affording the mono ‐ ortho ‐aminated benzamides only. The reaction tolerates a broad range of substrates with diverse functional groups and the corresponding ortho ‐aminated benzamides were efficiently synthesized in 41–82% yields. Abstract :